Sun impacts on ionized layers and transient variations of the earth's magnetic field Members of the Groupe International de Recherche en Géophysique Europe Afrique Asie - (:unkn) unknown (My University, 2015)
During the last decade in the projects IHY (International Heliophysical Year) 2005-2009 and ISWI (International Space Weather Initiative) 2010-2012, knowledge of the sun and its impacts on the ionized layers considerably progress following different ways: - Connecting the physical process from the sun to the ionosphere - Analysis of long series of ionospheric data over several solar cycles - Deployment of instruments (magnetometers and GPS) on the African continent in regions where measurements were nonexistent, thus leading to the revision of certain models. The research network GIRGEAA developed studies of equatorial Ionosphere in Africa and Asia. This presentation includes results on: - The time variations of ionosphere in Africa and Asia - The impacts of CME or high speed solar wind streams related to coronal holes on ionized layers (GPS/TEC measurements), - The magnetic DP2 current system related to the prompt penetration of magnetospheric convection electric field - The magnetic disturbance Ddyn associated to storm winds generated by Joule heating in the auroral zone: data analysis and modeling - The equatorial electrojet - etc.
Keywords: African Research